Konsep Pemimpin Adil Ibnu Taimiyah dan Relavansinya dengan Demokrasi Indonesia - Nur, Awaluddin; Ramadhani, Mutiara Ivonne; Kurniati (Archipelago Journal of Southeast Asia Islamic Studies, 2025)
Democracy in Indonesia faces several major problems and challenges, including rampant corruption, persistent social and economic inequality, political polarization that affects national stability and consensus-building, as well as an inefficient bureaucracy that hampers democratic progress. This study explores the concept of just leadership according to Ibn Taymiyyah and its relevance to Indonesia’s democratic system. Using a qualitative approach with a literature study method, the research aims to identify how principles of justice in leadership can strengthen democracy in Indonesia. The findings suggest that Ibn Taymiyyah’s ideas can enrich the Indonesian democratic framework, especially in terms of justice, offering a significant contribution to the development of Islamic leadership studies and democracy in the country. His emphasis on honesty and justice in governance, the establishment of an Islamic state to uphold Islamic law, and the necessity of the state to protect religion and society align with Indonesia's democratic aspirations. The study concludes that Ibn Taymiyyah’s principles of just leadership remain relevant and applicable to Indonesia’s governance, particularly in the context of elections.